Analysis of Supply Chain Risk Control in Aceh Nut Work Using the House Of Risk Method Approach (Case Study: Nutmeg Oil Industry in South Aceh Regency) - Dian Maulina; HY Sastra; M Dirhamsyah (Jurnal Inotera, 2023)
South Aceh nutmeg oil plays an important role in the trade of essential oils from Indonesia. 70-80% of Indonesia's nutmeg oil trade comes from South Aceh. However, on the other hand, there is a disruption in price stability in the production of South Aceh nutmeg oil which is influenced by the quality standards of nutmeg oil. The purpose of this study is to identify potential risks that arise in the supply chain, find risk agents as the cause of the risk and control the risk by designing risk mitigation and its formulation in the structure of the nutmeg oil supply chain in South Aceh. The technique used in this study is the House Of Risk (HOR) method. The study has obtained 23 risk events and 17 priority risk agents covering Source, Make, Distribution and Costumer (Return) activities. Then from the risk agents obtained, 11 priority mitigation actions were also obtained as a control of the performance of the nutmeg oil supply chain that can be applied in an effort to reduce the occurrence of supply chain risks so that the industry is able to produce optimally and is able to improve the quality of nutmeg oil which of course has a positive impact on the selling value.